Neonatal Encephalopathy: Need for Recognition of Multiple Etiologies for Optimal Management - Aslam, Saima; Strickland, Tammy; Molloy, Eleanor J. (Frontiers in Pediatrics, 2019)
Neonatal encephalopathy (NE) is associated with high mortality and morbidity. Factors predisposing to NE can be antenatal, perinatal or a combination of both. Antenatal maternal factors, familial factors, genetic predisposition, hypoxic ischemic encephalopathy, infections, placental abnormalities, thrombophilia, coagulation defects and metabolic disorders all have been implicated in the pathogenesis of NE. At present, therapeutic hypothermia is the only treatment available, regardless of aetiology. Recognising the aetiology of NE involved can also guide investigations such as metabolic and sepsis workups to ensure optimal management. Understanding the aetiology of NE may allow the development of targeted adjunctive therapies related to the underlying mechanism and develop preventative strategies